Edukasi Upaya Pencegahan Hipertensi Dengan Senam Lansia Dan Relaksasi Otot Progresif Pada Lansia Di Posyandu Lansia Desa Sundul Kecamatan Parang Kabupaten Magetan - Devita Anugrah Anggraini; Dian Anisia Widyaningrum (Lembaga Pengembangan Kinerja Dosen, 2023)
Hypertension is one of the PTM which is a threat, especially the elderly. Sundul Village is one of the villages in Parang District, Magetan Regency, East Java Province. The problem from the results of the study in Sundul Village is that there are still many people, especially the elderly who have hypertension and a lack of understanding in preventing hypertension, which is 75% or 60 out of 80 elderly. The purpose of community service is to increase knowledge related to efforts to prevent hypertension. The implementation method uses health education in the form of knowledge about hypertension with leaflet media given to the elderly and doing elderly gymnastics and progressive muscle relaxation. Previously, blood pressure was measured. Activities carried out on elderly aged> 40 years as many as 30 elderly. The results of the activity are that the elderly know about hypertension prevention, namely 75% of 30 elderly are able to understand and the elderly are able to do elderly gymnastic activities and progressive muscle relaxation. Seniors play an active role in this activity.